Design of Student Apartment Housing in Medan City, North Sumatra with A Green Architecture Theme - Fanny Fadillah; Melly Andriana; Dara Wisdianti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The increasing number of students in major cities such as Medan has created an urgent need for temporary housing that is adequate, comfortable, and sustainable. In response, the Indonesian government, through the Ministry of Public Works and Public Housing (PUPR), launched the